Magical Ways of Children’s Treatment in Slobozhanshchyna (based on field researches) - Ганус, Дзвенислава (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The paper describes features of folk pediatrics of Slobozhanshchyna population on the basis of field ethnographic materials. Main causes of the most common childhood diseases are considered. Methods for treatment of insomnia, «the evil eye», fear and epilepsy are examined. It is found out that magical part of «treatment» was mostly aimed at the «expulsion» of the disease from the body of the baby and sending it to another world.